Essays on health and health care utilization in Botswana - Mmopelwa, David (2021)
The role of health in both economic growth and development has been established in the literature. Consequently, public health policies aim to ensure an equitable provision of quality curative health services and promotion of preventive care. However, some national survey-based health indicators in Botswana show that both child and adult health deteriorated over time, which warrants investigation that is now timely given that both the current health policy and the integrated health service plan are nearing their end. Therefore, this three-essay thesis attempts to provide insights into deteriorating health.